Pt nanoparticles modified Au dendritic nanostructures: Facile synthesis and enhanced electrocatalytic performance for methanol oxidation. (24th August 2017) - Jia, Hongmei; Chang, Gang; Shu, Honghui; Xu, Maji; Wang, Xunying; Zhang, Zaoli; Liu, Xiong; He, Hanping; Wang, Kai; Zhu, Ruizhi; He, Yunbin
Abstract: A facile and simple method is presented for the synthesis of bimetallic composites, Pt nanoparticles modified dendritic Au nanostructures (PtNPs/DGNs), in which dendritic Au was deposited on a glassy carbon electrode via a potentiostatic method and sphere-like Pt nanoparticles were decorated on Au substrates through a chemical reduction reaction. The compositions, morphologies, and structures of the PtNPs/DGNs were characterized by X-ray photoelectron spectroscopy, field emission scanning electron microscopy, and energy dispersive X-ray spectroscopy. Results indicated that bimetallic composites were successfully synthesized and spherical Pt nanoparticles were dispersed evenly on dendritic Au substrates. The number of Pt nanoparticles on Au surface was regulated by controlling the chemical reduction deposition time, allowing the electrocatalytic properties of the composite towards methanol oxidation to be tuned. Electrochemical measurements, including cyclic voltammetry and chronoamperometry, were performed to investigate the electrochemical properties and electrocatalytic behaviors of the PtNPs/DGNs towards methanol oxidation. Pt nanoparticles partially covered dendritic Au exhibited dramatically enhanced electrocatalytic activity (3.947 mA cm −2 ), which was 2.65 times that of commercial carbon-supported Pt nanoparticles (1.487 mA cm −2 ), along with much improved poisoning tolerance (current decline: 70.85% vs 99.36%). These enhanced performances were likely caused by the large active electrochemical area of the bimetallic nanocomposites and the change in the electronic structure of Pt when the Au surface was modified with fewer Pt nanoparticles. Highlights: Pt nanoparticles modified dendritic Au nanostructures were obtained via a facile method. Pt NPs amount on Au can regulate electrocatalytic properties towards methanol oxidation. PtNPs/DGN showed superior electrocatalytic activity due to synergistic effect of Au and Pt. PtNPs/DGN exhibited good long-time stability and high poison tolerance for methanol oxidation.